EFFECT OF ETHANOLIC EXTRACTS OF LEAF AND FRUIT OF TRICHOSANTHES DIOICA AND LEAF OF CLITORIA TERNATEA ON SERUM LIPIDS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - R. KAVITHA (International Journal of Pharma and Bio Sciences, 2015)
Trichosanthes dioica and Clitoria ternatea were traditional plants that were used for the treatment of diabetes mellitus, stress and depressant. The present work was undertaken to evaluate the antihyperlipidemic effect of individual and combined ethanolic extracts of these two different herbs to study the acute oral toxicity study, body weight, oral glucose tolerance test and serum lipids in normal and STZ-induced diabetic rats. The extracts were administered orally to the diabetic animals for 28 days, resulted in a significant increase of body weight, decrease of blood glucose, total cholesterol, triglycerides, LDL, VLDL and phospholipids and significant increase of HDL. From the study it was revealed that combined plant extract was more effective for controlling serum lipids